Pesticide Formulations and Application Systems: Third Symposium 1983
DOI: 10.1520/stp32485s
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Droplet Spectra and Spray Recovery as a Function of Atomizer Type and Fluid Physical Properties

Abstract: Drop size, as indicated by the volume median diameter (VMD), and size uniformity, noted by the relative span (RS), were correlated with (1) viscosity, (2) surface tension, (3) viscoelasticity, and also (4) liquid throughput. Two types of nozzles were used, simple orifices or jets and hollow cones. The density of the mixtures did not vary greatly and no correlations were made with this function. Increased liquid throughput (increased orifice diameter) showed significant effects on drop size, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 2 publications
1
9
0
1
Order By: Relevance
“…Similar results were found by Yates et al (1976). Haq et al (1983) confirmed the basic relationship between liquid characteristics, nozzle type, and the effect of airstream shear by adding methanol to water to decrease the surface tension of the solution. They showed that increasing the surface tension of the solution from 20 dynes cm"' to 75 dynes cm"', increased the spray droplet vmd almost two-fold.…”
Section: Influence Of Droplet Surface Tension On Sprav Driftsupporting
confidence: 53%
See 2 more Smart Citations
“…Similar results were found by Yates et al (1976). Haq et al (1983) confirmed the basic relationship between liquid characteristics, nozzle type, and the effect of airstream shear by adding methanol to water to decrease the surface tension of the solution. They showed that increasing the surface tension of the solution from 20 dynes cm"' to 75 dynes cm"', increased the spray droplet vmd almost two-fold.…”
Section: Influence Of Droplet Surface Tension On Sprav Driftsupporting
confidence: 53%
“…An increase in spray liquid viscosity results in the formation of larger droplets (Liljedahl, 1971). However, Haq et al (1983) found that increasing the spray solution viscosity by adding glycerol to water either had little effect on droplet size or increased the percentage of drops less than lOOjLtm in diameter. Akesson and Gibbs (1990) concluded that viscosity is effective in changing droplet size only when large changes occur from the addition of special additives such as spray thickeners, particulating agents, and foaming agents or when invert emulsions are used.…”
Section: Influence Of Liquid Viscosity On Sprav Driftmentioning
confidence: 98%
See 1 more Smart Citation
“…Drift retardants were reported to reduce spray drift in many laboratory studies (Yates et al, 1976;Haq et al, 1982;Ozkan et al, 1992;Salyani and Cromwell, 1992;Smith, 1993). Laboratory tests indicated that drift retardants increased the volume median diameter of spray initially, but most polymer-based drift retardants lost effectiveness when recirculated through pumps (Bouse et al, 1988;Reichard et al, 1996;Zhu et al 1997).…”
mentioning
confidence: 99%
“…Existen numerosos estudios sobre la influencia de las propiedades físicoquímicas del caldo en las distintas fases de la pulverización, principalmente sobre el espectro de los tamaños de las gotas pulverizadas y sobre la distribución de la deposición sobre el objetivo (Haq et al, 1983;Yates et al, 1983;Bouse et al, 1986Bouse et al, , 1988Bouse et al, y 1990Salyani, 1988;Wirth et al, 1991;Stevens, 1993;Schick, 1997Schick, y 2006Zhu et al, 1997;Hall et al, 1993;Butler-Ellis et al, 1997;Butler-Ellis y Tuck, 1999;Miller y Butler-Ellis, 2000;Jørgensen, 2000;Butler-Ellis et al, 2001;Holloway et al, 2000;Hewitt, 2001;Stainier et al, 2006;Zabkiewicz, 2007). Las características que más influyen sobre ambos aspectos son la tensión superficial, principalmente la dinámica, y, en menor medida, la viscosidad del caldo.…”
Section: La Formulación Del Producto Fitosanitariounclassified